THE EFFECT OF BIG BOOK MEDIA ON INCREASING SPEAKING ABILITY AND SELF-CONFIDENCE IN EARLY CHILDREN - Rosida; Rachma Hasibuan (Adisam Publisher, 2024)
The aim of this research is to find out how much influence Big Book media has on improving speaking skills and self-confidence in young children. Research method design The research uses the Pre Experimental Design research type with the One Group Pre test and Post Test Design model. Where this research only uses one experimental group to measure the dependent variable (pre-test), then give a stimulus, and measure the dependent variable again (post-test), without any comparison group. The sample that will be used for research on the use of the Big Book is a total of 15 students out of 30 students in group A Kindergarten Al Hikmah Ketapang Banyuwangi. The research results are expected to show that there is a significant influence between the use of the Big Book on improving speaking skills and self-confidence in young children who are registered as group A students at Al Hikmah Kindergarten Ketapang Banyuwangi. Based on the findings of this research, it is recommended that early childhood teachers use Big Book media as an alternative in the learning process, in order to develop speaking skills and self-confidence in young children.